2020
DOI: 10.3126/nh.v14i1.30600
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Efficacy of Trichoderma spp. Against Phytophthora Blight of Pepper

Abstract: Phytophthora blight (PB) caused by Phytophthora capsici Leonian is an economically important disease of pepper in Nepal. Experiments were conducted in epiphytotic conditions at Luvu, Lalitpur where severe outbreak of PB used to occur. The experiment was designed in randomized complete block with three replications. Three isolates of Trichoderma harzianum viz, T. harzianum (T22), T. harzianum (T69), and T. harzianum and one isolate of T. asperellum, were tested for their efficacy under the field conditions comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This could be due to location specific and adaptation of Trichoderma isolates to the environmental conditions of that area. Past studies also suggest that the native Trichoderma isolates may possess greater potential against plant diseases (El‐Naggar et al, 2016; Promwee et al, 2017; Timila et al, 2015). That could be due to easy colonization by native Trichoderma in ecological niches where they belong to compared with the environment new to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to location specific and adaptation of Trichoderma isolates to the environmental conditions of that area. Past studies also suggest that the native Trichoderma isolates may possess greater potential against plant diseases (El‐Naggar et al, 2016; Promwee et al, 2017; Timila et al, 2015). That could be due to easy colonization by native Trichoderma in ecological niches where they belong to compared with the environment new to them.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of Trichoderma isolates on the lesion size (cm 2 ) of potato late blight (Phytophthora infestans) on detached leaf assay in cv.MS-42.3. plant diseases (El-Naggar et al, 2016;Promwee et al, 2017;Timila et al, 2015). That could be due to easy colonization by native Trichoderma in ecological niches where they belong to compared with the environment new to them.Yao et al (2016),Qu et al (2014) andZegeye et al (2011) studied the antagonist effect of native Trichoderma isolates and found significant results against late blight of potato.…”
mentioning
confidence: 99%